Evaluation of bio-engineered corneal scaffold for the repair of corneal defect in rabbit model - SANGEETHA, P; MAITI, S K; GAUTAM, PANKAJ; SINGH, KIRANJEET; GOPINATHAN, ASWATHY; SINGH, K P; MOHAN, DIVYA; NINU, A R; KUMAR, NAVEEN (The Indian Journal of Animal Sciences, 2017)
Clinically healthy adult New Zealand white rabbits (27) of either sex, were randomly divided into three groups (A, B and C) having 9 animals each. Porcine cornea was made acellular by treating it with 1% sodium dodecyl sulphate (SDS). Rabbit bone marrow derived mesenchymal stem cells were seeded over this acellular matrix. A 5mm diameter lamellar keratectomy wound was created over the peripheral cornea of rabbits in all the 3 groups. In group A, the corneal defect was managed by simple tarsorrhaphy without any graft and is treated as control. In group B, defect was repaired with decellularized porcine cornea and in group C, corneal defect was repaired with r-MSC seeded decellularized cornea. On the basis of clinical, pathological and scanning electron microscopic examinations, mesenchymal stem cell seeded corneal scaffold showed better healing and vision when compared to nonseeded scaffolds. Cell seeded corneal matrix was found to be an alternative to conventional means of surgical management of corneal ulcer.